Analyze the Role of Tourist Motivation toward Satisfaction and Identification the Push and Pull Motivational Factors among Bandung Tourist - Mandala, Rizky Yudistira; Hudrasyah, Herry (Journal of Business and Management, 2016)
Abstract. In the upcoming 2019, the Indonesian government is targeting an increase in the contribution of the tourism industry to be 8% for the total economy of Indonesia. The target that requested by the government makes a lot of development in the field of tourism industry. Data provided by the Central Bureau of statistic Indonesia showed a rise in the number of accommodation in the form of his hotel in every year in every province in Indonesia. This situation makes competition in the field of tourism industry in Indonesia is getting tight. The tourist motivation that could be a push factor to go on a trip and be a pull factor in deciding the travel destination that they want to visit can affect their satisfaction levels in their traveling activity. Another factor that examined in this study is travel experience of tourists who visit the city of Bandung for their holiday / vacation. The results of this study showed that the majority of tourists motivated by desire for relaxation, the reason that lead the tourist to a need of relaxation is their hometown atmosphere that make them bored of it. Other factors that attract tourists to visit the city of Bandung is the culinary tourism in Bandung. Many of the travelers who chose Bandung as a travel destination, they spend most of their time to visit cafes and restaurants. Motivation and experience that use to measure the tourist satisfaction shows that there is a positive effect from the tourist motivation and tourist experience to the tourist satisfaction. Although there is a positive influence from tourist motivation to the to the tourist satisfaction, the results of this study show that, the direct influence that was brought by the tourist motivation to satisfaction of travelers is smaller when compared with indirect influence on the tourist motivation to tourist satisfaction that through tourist experience. With the results of this study, recommended to the marketing department of the Bandung tourism industry to keep maintaining tourist experience from the tourists and also pay attention to the motivation that makes them traveled in Bandung, because when the motivation they met in a tourist area, then satisfaction rating will also increaseKeywords: Tourist, Motivation, Experience, Satisfaction, Push and pull theory, Bandung.